Effects and clinical outcomes of early initiation of sacubitril/valsartan in patients with chronic heart failure with a low ejection fraction - Z. D. Kobalava; S. A. Galochkin; V. V. Tolkacheva; N. Kh. Bagmanova (RUDN Journal of Medicine, 2020)
Aim : to evaluate effects and clinical outcomes of early initiation of sacubitril/valsartan in patients with chronic heart failure with a low ejection fraction. Methods : 30 patients admitted to the clinic for an episode of acute heart failure (AHF) II-IV class NYHA and decreased ejection fraction 40% (83.3% of men, mean age 66.0 [58.0-76.0] years) were included into the open study. Patients received the first dose of the study drug no later than 6 hours before discharge from the hospital. The period of active treatment was 26 weeks. At week 12 and 26, the number of patients receiving the target dose of 400 mg/day, as well as the dynamics of symptoms and severity of heart failure (HF) were evaluated. During the entire period of the study, safety parameters were investigated in all patients. Results . 70% of patients (n=21) received the target dose by week 2 77,8% (n=21) received the target dose of 200 mg 2 times a day at week 26. The positive effect in the dynamics of symptoms, as well as the severity of HF in the vast majority of patients were observed, a significant reduction in the severity of the main symptoms of HF was achieved, patients moved to a lower class of HF. 3 patients dropped out due to adverse events (1) and serious adverse events (2). 27 (90%) patients completed the program in accordance with the Protocol. Conclusion . Sacubitril/valsartanis is well tolerated, effective and safety drug in patients with CHF and a low ejection fraction.